Makna Spiritual Aku Hitam dalam Teks Kidung Agung 1:6 - Fransiska Juliawati; Hendi (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2022)
The article is a commentary on the Spritual significance in the song of Solomon 1:6 based on Origen view of the song of song commentary and homilies origen and another book by Gregory of nysa as homilies on the song of song. It was a book that blotted out the black spiritual significance of the song of Solomon. Many of god’s servants today have been inspired to convey only the literal meaning of the song of Solomon, and are then complemented by the experience and testimony of that servant of God. With the intent of making the hearts of the congregation rejoice even if the message of the text that is presented is irrelevant to the lives of the congregation the servants of the Lord often underestimate or take for granted the spiritual meaning of the song of Solomon because it is viewed only as a song representing the love of a man and a woman who love each other. There are not few servants of the Lord who view the text of the song of Solomon as relevant only to married congregations or to those in their 17th year of age or older. Because it’s so rare that the song of Solomon is preached because it is considered irrelevant in the modern age because it is just plain. This was the basic for the writer’s conception to discuss the book song of Solomon 1:6. Artikel ini adalah sebuah ulasan tentang Makna Spritual Dalam Kidung Agung Ps. 1:6 pandangan berdasarkan Origen dengan judul The Song of Songs Commentary and Homilies Origen dan buku lain oleh Gregory of Nysa yaitu Homilies on the Song of Songs. Yaitu sebuah buku yang membahas mengenai makna spiritual hitam dalam kitab kidung agung. Kebanyakan di zaman sekarang ini banyak hamba Tuhan yang hanya menyampaikan makna dari teks Kidung Agung secara literal saja, kemudian di lengkapi dengan pengalaman serta kesaksian hamba Tuhan tersebut. Dengan maksud membuat hati para jemaat menjadi senang meskipun pesan dari teks yang disampaikan tidak relevan dengan kehidupan jemaatnya. Hamba Tuhan seringkali menyepelekan atau tidak serius dalam menyampaikan makna spiritual dari teks Kidung Agung, karena dianggap hanya sebagai suatu nyanyian yang melambangkan antara cinta seorang pria dan wanita yang saling mencintai. Tidak sedikit hamba Tuhan yang berpandangan bahwa teks Kidung Agung ini dianggap relevan hanya bagi jemaat yang sudah berkeluarga atau kepada jemaat yang sudah menginjak usia 17 tahun ke atas. Oleh sebab itu Kidung Agung sangat jarang di khotbahkan karena dianggap tidak relevan di zaman kekinian sebab hanya ditujuhkan kepada kalangan-kalangan tertentu saja. Pandangan ini merupakan pandangan yang dangkal karena salah diartikan. Hal itulah yang mendasari penulis sehingga penulis tertarik untuk membahas kitab kidung agung 1:6.